PENGARUH PENGGUNAAN APLIKASI GOOGLE CLASSROOM TERHADAP HASIL BELAJAR IPA KELAS VA SDN KEMBANGAN UTARA 012 PETANG - Fitria Fitria; Ainur Rosyid (Jurnal Inovasi Penelitian, 2021)
This study aims to determine the effect of using the Google Classroom application on science learning outcomes for class VA at SDN Kembangan Utara 012 Petang. This research is a quantitative research using survey method. The population in this study was class VA students, totaling 32 students. The data collection technique in this study was using a questionnaire. Information obtained from respondents using this questionnaire is used to find the effect of using the Google Classroom application on science learning outcomes. This study uses a partial test (t test) to determine the hypothesis. The results of the hypothesis obtained based on the partial test (t test) are 3,655 (tcount) > 2,042 (ttable) with a significance of 0.000 < 0.005. These results indicate that H1 is accepted and Ho is rejected, which means that there is a positive and significant effect between the use of the Google Classroom application on the science learning outcomes of class VA students at SDN Kembangan Utara 012 Evening.